2020
DOI: 10.12973/eu-jer.9.2.835
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Assessment of the Social Media Motives Scale among University Students

Abstract: Social media (SM) use is a rapidly growing phenomenon among Millennials. Thus, a growing body of studies have explored the beneficial applications and negative consequences of their use in an increasingly virtual world. The current study aimed to develop and validate a scale that measures university students' motives for using SM from a psychological and social perspective. In Study 1 (N = 316), the psychometric properties of SM motives were examined. The estimated factorial structure was validated in Study 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…One previous study (Crocker & Mazer, 2019) indicated that career development trends in the current decade will be led by technologically oriented professions. In line with this, according to a previous study, many young people and entrepreneurs are developing their careers and businesses in this direction (Alhadabi & Karpinski, 2020). The following comments from participants illustrate this trend, I want to become a Youtuber after university … I will make my own videos and upload them online … my home and my room is my office … I don't need to go to an office or classroom for any purpose … I enjoy this working environment.…”
Section: Career Interests and The Distance Learning Modelmentioning
confidence: 62%
See 1 more Smart Citation
“…One previous study (Crocker & Mazer, 2019) indicated that career development trends in the current decade will be led by technologically oriented professions. In line with this, according to a previous study, many young people and entrepreneurs are developing their careers and businesses in this direction (Alhadabi & Karpinski, 2020). The following comments from participants illustrate this trend, I want to become a Youtuber after university … I will make my own videos and upload them online … my home and my room is my office … I don't need to go to an office or classroom for any purpose … I enjoy this working environment.…”
Section: Career Interests and The Distance Learning Modelmentioning
confidence: 62%
“…In past decades, most careers and job roles have been based on site and are likely to require in-person attendance. However, due to the development of technology and social media applications (Alhadabi & Karpinski, 2020), many jobs are now fully remote and available online. Many participants said they intended to work remotely or become full-time home workers after graduation, as set out below, I don't want to work in the traditional office environment with other co-workers and supervisors … I want to work in my own office and start my own solo business … this is the trend of the current decade … I think this online degree meets my needs… (Participant #1,Interview Session) People have their own ways and wants for working … I want to work at home … I don't want to take the commuter rail every day from my home to the city … I am an adult; I can select my online degree and I want to select my job as well… (Participant #45,Interview Session) The views expressed by the participants suggest that there has been a change in the career interests and trends of contemporary learners (i.e.…”
Section: Career Interests and The Distance Learning Modelmentioning
confidence: 99%
“…On Instagram, motivations encompass passing time, social interaction, self-presentation, and entertainment. Likewise, Alhadabi & Karpinski's [10] study explores the creation and validation of a scale measuring university students' motives for using social media. Study 1 (N = 316) identified five motive scales: self-actualization, purposeful motives, enjoyment, self-enhancement, and convenience.…”
Section: -1-motivation For Using Social Media (Mov)mentioning
confidence: 99%
“…In many different fields, such as education (Alshalawi, 2022;Malik et al, 2018;Muste, 2016), health (Alhadabi & Karpinski, 2020;Khamis & Geng, 2021;Kondo et al, 2020;Leal-Costa et al, 2020), and business (Krishnan et al, 2019;Ulas & Akinci Vural, 2019), the significance of having strong communication skills is readily apparent. There is a correlation between developing and maintaining excellent communication skills and higher academic success (Mohammed, 2015), greater employability (Clokie & Fourie, 2016), and enhanced leadership abilities (Yuningsih & Mulyana, 2017), all of which contribute to an individual's personal development and professional progression.…”
Section: Research Articlementioning
confidence: 99%